Effects of the biodegradation on biodegradable polymer blends and polypropylene - Pereira, R. C T [UNESP]; Franchetti, S. M M; Agnelli, J. A M; Mattoso, L. H C (AIP Publishing, 2008)
The large use of plastics in the world generates a large amount of waste which persists around 200 years in the environment. To minimize this effect is important to search some new polymer materials: the blends of biodegradable polymers with synthetic polymers. It is a large area that needs an Intensive research to investigate the blends properties and its behavior face to the different treatments to aim at the blodegradation. The blends used In this work are: some blodegradable polymers such as: poly(hydroxybutyrate) (PHB) and poly(s-polycaprolactone) (PCL) with a synthetic polymer, polypropylene (PP), in lower concentration. These blends were prepared using an internal mixer (Torque Rheometer), and pressed. These films were submitted to fungus biotreatment. The films analyses will be carried out by Fourier Transform Infrared (FTIR), UV-Vis absorption (UV-Vis), Scanning Electronic Microscopy (SEM), DSC and TGA. © 2008 American Institute of Physics.